Analisis Kinerja MIMO Masif dengan Teknik Precoding Maximum Ratio Transmission - Rusdha Muharar (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Channel State Information (CSI) at the base stations obtained via the uplink trainingis an important factor in cellular and multiuser Multi-Input Multi-Output (MIMO) communi-cation networks. In massive MIMO cellular networks with pilot-based training, the most adopted approach is to employ the sameset of orthogonal training symbols in each cell. This is called the full-pilot reuse (FPR) scheme. In this paper, we consider the less-common but a more practical approach where each cell uses different sets of orthogonal training symbols and call this scheme as the Different Orthogonal Pilot (DOP) sequences. In particular, we focus on the downlink performance of massive MIMO networks with the Maximum Ratio Transmission (MRT) precoder at the base stations. The analysis is performed in the large system regime where the number of antennas at each base station and the number of users at each cell tend to infinity with a fixed ratio. We obtain a new expression for the Signal to Interference plus Noise Ratio (SINR) in that regime, called the limiting SINR. Numerical simulations show that it can approximate the finite-size systems accurately. Furthermore, the simulations also indicate that the DOP scheme can give a better SINR and a higher user capacity compared to those of the FPR scheme.